2021
DOI: 10.1038/s41598-021-96709-6
|View full text |Cite|
|
Sign up to set email alerts
|

The RhoA dependent anti-metastatic function of RKIP in breast cancer

Abstract: Raf-1 kinase inhibitor protein was initially discovered as a physiological kinase inhibitor of the MAPK signaling pathway and was later shown to suppress cancer cell invasion and metastasis. Yet, the molecular mechanism through which RKIP executes its effects is not completely defined. RhoA has both a pro- and anti-metastatic cell-context dependent functions. Given that Rho GTPases primarily function on actin cytoskeleton dynamics and cell movement regulation, it is possible that one way RKIP hinders cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Both RKIP and E-cadherin are tumor suppressors, and as such, there has been shown a positive correlation between the two, with both having decreased expression in cancer as invasion and metastasis increased [ 184 ]. RKIP in addition to expression correlations, also has a regulatory effect on E-cadherin, acting as an upstream activator [ 185 ]. In particular, in RKIP knockout studies, RKIP has been shown to activate RhoA, a negative regulator of breast cancer, which in turn, stabilizes E-cadherin in adherens junctions and regulates E-cadherin localization to the membrane [ 185 ].…”
Section: Crosstalk Between Rkip and Known Emt Regulatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both RKIP and E-cadherin are tumor suppressors, and as such, there has been shown a positive correlation between the two, with both having decreased expression in cancer as invasion and metastasis increased [ 184 ]. RKIP in addition to expression correlations, also has a regulatory effect on E-cadherin, acting as an upstream activator [ 185 ]. In particular, in RKIP knockout studies, RKIP has been shown to activate RhoA, a negative regulator of breast cancer, which in turn, stabilizes E-cadherin in adherens junctions and regulates E-cadherin localization to the membrane [ 185 ].…”
Section: Crosstalk Between Rkip and Known Emt Regulatorsmentioning
confidence: 99%
“…RKIP in addition to expression correlations, also has a regulatory effect on E-cadherin, acting as an upstream activator [ 185 ]. In particular, in RKIP knockout studies, RKIP has been shown to activate RhoA, a negative regulator of breast cancer, which in turn, stabilizes E-cadherin in adherens junctions and regulates E-cadherin localization to the membrane [ 185 ]. RKIP regulates E-cadherin through Erk2 in the MEK/ERK pathway as well since RKIP inhibits the activation and phosphorylation of Erk2 [ 185 ].…”
Section: Crosstalk Between Rkip and Known Emt Regulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been confirmed that the activation of RhoA and Rac1 enhanced the migration of colorectal Frontiers in Pharmacology frontiersin.org cancer (Xie et al, 2021) (Wufuer et al, 2021). Other researchers have found that inhibition of Cdc42 was responsible for the suppression of invasion ability in lung cancer (Li et al, 2021), while the reduced RhoA had an anti-metastatic function on breast cancer (Kalpana et al, 2021). Further research suggests that Rho GTPases directly affect the plasticity of cells and promote cell movement by remodeling the cytoskeleton.…”
Section: Discussionmentioning
confidence: 89%